A qualitative examination of football players’ acceptability and perceptions on the use of virtual reality in football training - Anna U. Shields; David L. Neumann; Matthew J. Stainer (PLoS ONE, 2025)
Introduction Virtual reality (VR) technologies are being increasingly used for training among football teams. Despite this, limited research has examined football players’ acceptability and perceptions of VR training. It is essential to understand football players’ perspectives on this training approach to identify any psychological factors that may influence its uptake. Methods A qualitative approach was adopted to explore footballers’ acceptability and perceptions of VR in training. Fourteen professional and semi-professional football players completed a survey and took part in qualitative semi-structured interviews between May and October 2023. All participants were asked questions about their perspectives of the benefits and barriers of using VR for football training. The interview data was recorded and analysed using reflexive thematic analysis. Results Themes regarding the footballers’ acceptability were interpreted within the framework of the Technology Acceptance Model. Overall, the footballers demonstrated acceptability and emphasised its potential usefulness in football training. Footballers perceived VR as being beneficial for cognitive and perceptual-motor skill training, mental preparation and pressure training through exposure to representative game-like environments, as well as providing greater training flexibility. Alongside these benefits, factors which could hinder optimal uptake were identified, including lack of accessibility, financial costs, and perceptual differences between the VR environments and the real-world. Conclusion The present study provides insight into experienced football players’ acceptability and perceptions of VR for training and suggest that VR training has potential to be accepted by football players, particularly when it is promoted to them as a flexible approach that can enhance their on-field performance.